2020
DOI: 10.3390/molecules25153326
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Performance Evaluation of Asphaltenes-Modified Asphalt Binders

Abstract: Asphalt binder comprises four main fractions—asphaltenes (A), saturates (S), aromatics (A), and resins (R)—referred to as “SARA”. Asphaltenes plays an important role in determining the linear viscoelastic behavior of asphalt binders. In this research, asphaltenes are added as a distinct modifier to improve the performance properties of asphalt binder. The modified binders are aged using a rolling thin film oven. A dynamic shear rheometer is then used to measure the rheological properties of the binders at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…The amplitude sweep test shows that the process of chlorination does definitely change the G* and δ for these blends. This is supported by the results from references [13,5]. As such, it can be expected that chlorinated latex bitumen binders have potential application in the roofing applications.…”
Section: Rheologysupporting
confidence: 63%
See 1 more Smart Citation
“…The amplitude sweep test shows that the process of chlorination does definitely change the G* and δ for these blends. This is supported by the results from references [13,5]. As such, it can be expected that chlorinated latex bitumen binders have potential application in the roofing applications.…”
Section: Rheologysupporting
confidence: 63%
“…Another important property to get suitable performance requirements of bitumen pavement is asphaltene equilibrium. Previous research has indicated that increasing asphaltene contents decreases asphalt temperature susceptibility [13]. The asphaltene is the major responsible viscoelasticity of asphalt blends and raising the asphaltenes contents increases asphalt mixes stiffness and viscosity resulting in penetration and creep compliance decrease [13].…”
Section: Introductionmentioning
confidence: 99%
“…Difusi fraksi maltene dalam crumb rubber menyebabkan fenomena ekspansi volume (swelling) pada crumb rubber Xia et al, 2021). Fenomena swelling yang terjadi pada crumb rubber oleh fraksi maltene berdampak pada rasio asphaltene dalam aspal yang meningkat dan membuat aspal semakin keras (Ghasemirad et al, 2020). Kekerasan aspal meningkat setelah penambahan crumb rubber mengindikasikan bahwa rata-rata berat dan kerapatan molekul campuran aspal juga turut meningkat (Fang et al, 2016;Hofko et al, 2016).…”
Section: Titik Lembek (Softening Point) Aspal Modifikasi Crumb Rubber...unclassified
“…Preliminary studies [ 42 , 43 , 44 ] have been conducted to show that the asphaltene content affects the basic indices of penetration, softening point, Frass brittle point, etc. Among different structural fractions, asphaltenes display the lowest temperature susceptibility [ 45 ], and they significantly contribute to bitumen stiffness, rigidity, and elasticity [ 46 , 47 ]. Xin et al [ 48 ] further investigated the effect of polycyclic aromatic compounds (PAC), a major fraction of asphaltene, on asphalt, and found that the elasticity and complex modulus of asphalt were reduced with increasing PAC.…”
Section: Introductionmentioning
confidence: 99%